Motives of Tantrum Behavior Among Beneficiaries in Religious Guidance Programs at the Social Service and Rehabilitation Center for People - Azizah Atha; Gregory Ajima Onah (PT Pro Panoramic Solution, 2026)
This study examines the motives underlying tantrum behavior among beneficiaries participating in religious guidance programs at the Social Service and Rehabilitation Center for People with Social Welfare Problems (PRS PMKS) in Sidoarjo. Tantrum behavior, often interpreted as disruption or noncompliance, is analyzed sociologically as meaningful social action shaped by subjective motives, life experiences, and institutional interactions. Using a descriptive qualitative approach with a social phenomenological method, data were collected through passive observation, in-depth interviews with beneficiaries and religious instructors, and documentation. Data were analyzed through reduction, display, and conclusion drawing, and interpreted using Max Weber’s theory of social action, complemented by Michel Foucault’s concepts of disciplinary power and Pierre Bourdieu’s framework of symbolic power and religious field. The findings show that tantrum behavior is driven by emotional trauma, adjustment to institutional routines, instrumental considerations, and internalized moral values. Tantrum behavior functions as social communication, subtle resistance, and identity negotiation within institutional religious practices. Therefore, tantrum behavior should be understood as meaningful social action reflecting the interaction between individual agency, institutional power, and religious moral regulation in social rehabilitation.